Digital mining applications in distance education environments - Sevindik, Tuncay; Demirkeser, Necmi (ACADEMIC JOURNALS, 2010)
It is seen that distance education environments are more frequently used due to the progress of internet today. The data acquired from these environments are commonly irregular journal records and text-based communication messages. Digital mining applications are used in order to convert these irregular data into regular, and cleaning out the information stacks. The purpose of this research is to reveal the usage of the types of digital mining application, which are being applied within the distance education environments. For this purpose, a situation-based study was carried out which was related to the subjects of data mining, web mining and text mining, being used in the distance education environments. As a result of the research, a relationship was determined between the types of digital mining.
Keywords: Text mining; data mining; web mining; Science & Technology - Other Topics